Process transformation method for coal-fired boiler fly ash outlet equipment of thermal power plant
Patent Information
- Application Number
- CN202611301108.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-26
- Publication Date
- 2026-10-16
AI Technical Summary
然而,现有从粉煤灰中提取有价元素的技术路线普遍存在工艺流程长、酸碱消耗大、废水处理困难等问题
本发明从设备源头进行改造,在出灰口高温区直接进行粉料喷吹反应,改变了粉煤灰的物相和粒度,显著提升后续湿法浸出效率。
Smart Images

Figure CN122913202A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of coal-fired solid waste treatment and resource recycling technology, and in particular relates to a process modification method for fly ash outlet equipment of coal-fired boilers in thermal power plants. Background Technology
[0002] Fly ash is a major solid waste generated by coal-fired boilers in thermal power plants. Traditional treatment methods mainly involve landfilling and stockpiling, which not only occupy large amounts of land but also potentially cause soil and groundwater pollution. Currently, the comprehensive utilization of fly ash is mainly concentrated in the building materials sector (such as cement admixtures and blocks), with low added value. Fly ash contains silicon dioxide, alumina, and small amounts of rare metals and rare earth elements, possessing high potential resource value. However, existing technologies for extracting valuable elements from fly ash generally suffer from problems such as long process flows, high acid and alkali consumption, and difficulties in wastewater treatment. Furthermore, the original soot blowing devices at the boiler ash outlet only serve to remove accumulated ash and do not participate in phase regulation, leading to significant challenges in subsequent treatment. Therefore, developing a fly ash resource utilization technology that intervenes at the source, has a short process flow, and low emissions is of significant practical importance. Summary of the Invention
[0003] To address the aforementioned problems, this invention provides a method for modifying the process of fly ash outlet equipment in coal-fired power boilers. By adding a powder injection device to the soot blowing device at the boiler ash outlet, functional powders are directly mixed and reacted with fly ash at high temperatures, altering the phase composition and surface activity of the fly ash. Combined with steps such as water leaching, dilute acid leaching, concentrated acid leaching, and ion-exchange membrane separation, this achieves the preparation of silicon-based fertilizers, acid recycling, and the separation and recovery of rare earth / metal ions.
[0004] To achieve the above-mentioned objectives, the present invention adopts the following technical solution: A method for modifying the process of fly ash outlet equipment in a coal-fired boiler includes the following steps: injecting functional powder into the fly ash at the boiler ash outlet for high-temperature modification, and then subjecting the modified fly ash to water leaching, dilute acid leaching, and concentrated acid leaching in sequence. The leachate from each stage is recycled, and the solid from the concentrated acid leaching is used as a silicon-based product. Rare earth elements, valuable metal ions, and acid are recovered from the obtained concentrated acid leaching solution.
[0005] Furthermore, the method for modifying the process of the fly ash outlet equipment of the coal-fired boiler in thermal power plants specifically includes the following steps: S1. Install a powder injection system on the ash blowing device at the ash outlet of a coal-fired boiler to inject functional powder into the fly ash and directly carry out the powder injection reaction in the high-temperature zone of the ash outlet to obtain modified fly ash. S2. The modified fly ash obtained in step S1 is subjected to water leaching treatment, and liquid-solid separation is performed to obtain water leaching liquid and water leaching solid; the water leaching liquid is returned to step S1 as a carrier of the powder injection system or used to prepare leaching agent. S3. The water-soaked solid obtained in step S2 is subjected to dilute acid leaching treatment, and the liquid and solid are separated to obtain dilute acid leaching solution and dilute acid leaching solid; acid is added to the dilute acid leaching solution and it is recycled in the dilute acid leaching treatment. S4. The dilute acid leaching solid obtained in step S3 is subjected to concentrated acid leaching treatment, and the liquid and solid are separated to obtain concentrated acid leaching solution and concentrated acid leaching solid. The obtained concentrated acid leaching solid is washed and dried and used as silicon-based nutrient fertilizer or soil conditioner. Rare earth elements, valuable metal ions and acid are recovered from the concentrated acid leaching solution using an ion membrane separation system. The separated acid solution is returned to step S4 for recycling.
[0006] In the process modification method for fly ash outlet equipment of coal-fired boilers provided by this invention, the water leaching solution, dilute acid leaching solution, and concentrated acid solution are all recycled throughout the entire process, and almost no waste liquid is generated.
[0007] Furthermore, in step S1, the temperature of the high-temperature zone at the ash outlet is 650~800℃.
[0008] Functional powders are rapidly mixed with fly ash under high-temperature gas flow and undergo a solid-phase reaction, causing depolymerization or pre-activation of the aluminosilicate glass in the fly ash. Simultaneously, the particle size and phase composition of the products are controlled (e.g., generating nepheline and potassium feldspar intermediate phases), effectively reducing the strength of the silica-alumina network structure and improving subsequent leaching efficiency. The fly ash collected after this modification exhibits significantly enhanced reactivity, creating favorable conditions for subsequent wet processing.
[0009] Further, in step S1, the functional powder is selected from one or two of neutral alkali metal salts or alkaline alkali metal salts; the neutral alkali metal salts include NaCl and KCl; the alkaline alkali metal salts include Na2CO3 and K2CO3; The amount of neutral alkali metal salt added is 2-3% of the mass of fly ash; the amount of alkaline alkali metal salt added is 6-12% of the mass of fly ash.
[0010] Furthermore, in step S1, the particle size of the functional powder is <50 μm.
[0011] Further, in step S2, the water immersion treatment is performed by mixing the modified fly ash and water at a mass ratio of 1:(3~4) and stirring at 70~90℃ for 1~2 h.
[0012] Further, in step S3, the dilute acid leaching process is performed by mixing the water-leached solid and dilute acid at a mass ratio of 1:(3~5) and stirring at 70~85°C for 2 hours.
[0013] Furthermore, the dilute acid is selected from hydrochloric acid, sulfuric acid, or nitric acid; the concentration of the dilute acid is 0.2~0.6 mol / L.
[0014] Further, in step S4, the concentrated acid leaching process is performed by mixing the dilute acid leaching solid and concentrated acid at a mass ratio of 1:(2~3) and stirring at 90°C for 3~5 h.
[0015] Furthermore, the concentrated acid is selected from hydrochloric acid, sulfuric acid, or nitric acid; the concentration of the concentrated acid is 5~7 mol / L.
[0016] Furthermore, in step S4, an ion-exchange membrane separation system is used in the recycling process.
[0017] The ion-exchange membrane separation system employs a homogeneous cation exchange membrane and / or a homogeneous anion exchange membrane, with a current density of 300–600 A / m. 2 The system operates at a temperature of 35–50°C. It exhibits a rejection rate of ≥85% for aluminum and iron ions, a migration rate of ≥70% for titanium oxide and zirconium oxide ions, a recovery rate of ≥85% for rare earth ions, and a free acid recovery rate of ≥90%. The target ions selectively separated by the ion-exchange membrane separation system include Al... 3+ Fe 3+ TiO 2+ ZrO 2+ and La 3+ Ce 3+ Rare earth ions and Li + Ga 3+ Valuable metal ions.
[0018] Compared with the prior art, the present invention has the following advantages and technical effects: This invention modifies the equipment from the source, directly carrying out powder injection reaction in the high-temperature zone of the ash outlet, which changes the phase and particle size of fly ash and significantly improves the efficiency of subsequent wet leaching.
[0019] This invention uses neutral or alkaline alkali metal salts as functional powders, which are inexpensive and easily reused through subsequent water leaching, avoiding the introduction of difficult-to-remove impurities. The dosage of neutral alkali metal salts (NaCl, KCl) is strictly controlled at 2-3% to avoid the risk of corrosion to subsequent equipment due to excessive chloride ions, while still achieving a significant activation effect.
[0020] The wet treatment process in this invention uses a gradient leaching of water, dilute acid, and concentrated acid to achieve stepwise separation of valuable elements. The final solid silica can be directly used as silicon fertilizer, with no tailings discharge.
[0021] In this invention, all types of leachates are designed with circulation paths, which significantly reduces acid and water consumption and reduces the pressure on wastewater treatment.
[0022] In this invention, rare earth elements and rare metals in concentrated acid leachate are selectively recovered using ion-exchange membrane technology. The ion-exchange membrane separation system is specifically designed for Al. 3+ Fe 3+ TiO 2+ ZrO 2+ The parameters of the target ions were optimized, and the rare earth recovery rate reached over 85%, and the acid recovery rate was ≥90%, realizing the efficient separation of valuable elements and the recycling and high-value-added resource utilization of the medium.
[0023] The method provided by this invention requires minimal modification to existing thermal power plant soot blowing systems, has controllable investment and operating costs, and has good prospects for industrial promotion. Attached Figure Description
[0024] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings used in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.
[0025] Figure 1 The present invention provides a process flow diagram of a method for modifying the process of fly ash outlet equipment in a coal-fired boiler. Detailed Implementation
[0026] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as a limitation of the present invention, but rather as a more detailed description of certain aspects, features, and embodiments of the present invention.
[0027] It should be understood that the terminology used in this invention is merely for describing particular embodiments and is not intended to limit the invention. Furthermore, with respect to numerical ranges in this invention, it should be understood that each intermediate value between the upper and lower limits of the range is also specifically disclosed. Every smaller range between any stated value or intermediate value within a stated range, and any other stated value or intermediate value within said range, is also included in this invention. The upper and lower limits of these smaller ranges may be independently included or excluded from the range.
[0028] Unless otherwise stated, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art. While only preferred methods and materials have been described herein, any methods and materials similar or equivalent to those described herein may be used in the implementation or testing of this invention. All references to this specification are incorporated by way of citation to disclose and describe methods and / or materials associated with those references. In the event of any conflict with any incorporated reference, the content of this specification shall prevail.
[0029] Various modifications and variations can be made to the specific embodiments described in this specification without departing from the scope or spirit of the invention, as will be apparent to those skilled in the art. Other embodiments derived from this specification will also be apparent to those skilled in the art. This specification and embodiments are merely exemplary.
[0030] The terms “include,” “including,” “have,” “contain,” etc., used in this article are all open-ended terms, meaning that they include but are not limited to.
[0031] This invention provides a method for modifying the process of fly ash outlet equipment in a coal-fired boiler, comprising the following steps: S1. Modification of soot blowing device and powder injection reaction: A powder injection system is added in parallel or in series to the existing ash blowing device at the ash outlet of the coal-fired boiler. The powder injection system includes a powder silo, a metering feeder, an airflow pipeline, and a high-temperature resistant mixing nozzle. During the boiler ash discharge process, functional powders are injected into the high-temperature fly ash stream. The amount of neutral alkali metal salts (sodium chloride, potassium chloride) added does not exceed 2-3% of the fly ash mass; the amount of alkaline alkali metal salts (sodium carbonate, potassium carbonate) added is 6-12% of the fly ash mass. The ash outlet temperature is controlled at 650-800℃ by adjusting the cold air intake.
[0032] 2. Water immersion treatment and circulation: The modified fly ash obtained in step S1 is mixed with water at a mass ratio of 1:(3~4) and stirred at 70~90℃ for 1~2 hours, followed by liquid-solid separation. The resulting water-leached liquid mainly contains soluble alkali metal salts (such as potassium and sodium salts) and can be returned to step S1 as a carrier for the powder injection system or used to prepare leaching agents; the resulting water-leached solids proceed to the next step of processing.
[0033] S3. Dilute acid leaching treatment and circulation: The water-leached solid obtained in S2 is mixed with a dilute acid solution (such as dilute hydrochloric acid, dilute sulfuric acid, or dilute nitric acid) with a concentration of 0.2~0.6 mol / L at a mass ratio of 1:(3~5). The mixture is stirred at 70~85℃ for 2 hours, followed by liquid-solid separation. The separated dilute acid leachate mainly contains easily leached metal ions such as calcium, magnesium, iron, and aluminum. This solution is readjusted to its initial concentration by adding a small amount of concentrated acid and then recycled back to this step. The separated dilute acid-leached solid proceeds to the next step.
[0034] S4. Concentrated acid leaching treatment and ion-exchange membrane separation: The dilute acid-impregnated solid obtained from S3 is mixed with a concentrated acid solution (of the same type as the dilute acid) with a concentration of 5-7 mol / L at a mass ratio of 1:(2-3), stirred at 90℃ for 3-5 h, and then the liquid and solid are separated.
[0035] The resulting concentrated acid-leached solid is mainly enriched silica (SiO2 content ≥85%), which, after washing, drying and granulation, is used as a silicon-based nutrient fertilizer or soil conditioner.
[0036] The concentrated acid leachate contains aluminum ions (Al). 3+ ), iron ions (Fe 3+ ), titanium oxide ions (TiO2) 2+ ), zirconium oxide ions (ZrO) 2 + The leachate contains rare metals such as lithium, gallium, and germanium, as well as rare earth elements such as lanthanum and cerium. The leachate is introduced into an ion-exchange membrane electrodialysis separation system, using a homogeneous anion exchange membrane (model: DF-120) or a cation exchange membrane (model: CM-7000), operating at a current density of 300–600 A / m² and a temperature of 35–50℃. Based on differences in ion valence and migration rate, the following selective separation is achieved: trivalent ions such as aluminum and iron have low migration rates and are mostly retained in the separation chamber; divalent oxygen ions such as titanium oxide ions and zirconium oxide ions can selectively permeate through specific membranes; rare earth ions (La... 3+ Ce 3+ Due to their large hydration radius and high charge density, the separation efficiency of (etc.) ions can reach 85-95% under optimized conditions; valuable metal ions (Li... + Ga 3+ (etc.) can be enriched separately. The acid solution after separation by ion-exchange membrane (the acid concentration decreases by about 10~20%, and the free acid recovery rate is ≥90%) is returned to the S4 concentrated acid leaching section, and after replenishing concentrated acid, it is recycled.
[0037] In the process modification method for fly ash outlet equipment of coal-fired boilers provided in this embodiment of the invention, the acid solutions separated by ion-exchange membranes from the water leaching solution, dilute acid leaching solution, and concentrated acid leaching solution are all returned to the corresponding process section for recycling, and the amount of waste liquid discharged during the process is extremely low.
[0038] Figure 1 The present invention provides a process flow diagram of a method for modifying the process of fly ash outlet equipment in a coal-fired boiler.
[0039] The room temperature in this invention refers to 25±2℃.
[0040] The raw fly ash from a certain coal-fired power plant contains 55% SiO2, 26% Al2O3, 6% Fe2O3, 3% CaO, and approximately 280 ppm of rare earth elements (mainly Ce and La).
[0041] The embodiments and comparative examples of this invention are all based on the technological transformation of fly ash resource utilization in coal-fired boilers of thermal power plants. Examples 1 to 11 adopt the in-situ injection treatment process at the high-temperature ash outlet.
[0042] Example 1 A sodium carbonate powder injection device was installed next to the ash outlet blowing device. Na2CO3 powder with a particle size of <50μm was injected at 6% of the fly ash mass. Compressed air for blowing was used as the conveying air source. The mixture was mixed and reacted at 650℃ for 3h. The modified fly ash was collected and X-ray diffraction analysis was performed on the obtained modified fly ash. The results are shown in Table 1.
[0043] The modified fly ash was mixed with deionized water at a mass ratio of 1:3, stirred at 70°C for 1 hour, and then filtered for the first time. The resulting water leachate contained K. + Na + The high concentration is returned to the powder preparation system as a carrier for the powder injection system or used to prepare the leaching agent; the water-leached solid obtained from the first filtration is mixed with hydrochloric acid (0.6 mol / L) at a mass ratio of 1:3, stirred at 75°C for 2 hours, and then filtered a second time. The resulting dilute acid leachate (containing Fe) 3+ Al 3+ Hydrochloric acid is added until the HCl concentration in the dilute acid leachate reaches 0.6 mol / L, then the solution is recycled. The dilute acid leachate solid obtained from the second filtration is mixed with hydrochloric acid (5 mol / L) at a mass ratio of 1:3, stirred at 90℃ for 3 hours, and then filtered a third time. The concentrated acid leachate solid obtained from the third filtration is washed and dried to obtain a product with a SiO2 content of 82.5%, which is then granulated and used for wheat application. The concentrated acid leachate obtained from the third filtration is sent to an ion-exchange membrane electrodialysis unit. The rare earth enrichment solution is precipitated to obtain mixed rare earth oxides with a purity ≥82%. The acid solution is recovered and returned to the concentrated acid leachate process. The entire system requires only 220 kg of concentrated acid and a small amount of sodium carbonate (15% of the initial amount) to be added for every ton of fly ash processed, with no wastewater discharge.
[0044] The operating parameters and effects of ion-exchange membrane separation in this embodiment are as follows: The concentrated acid leaching solution (Al) of this embodiment 3+ 18.2 g / L, Fe 3+ 3.7 g / L, TiO 2+ 0.9 g / L, ZrO 2+ (0.28 g / L, total rare earth content 487 mg / L) was fed into the ion-exchange membrane electrodialysis system.
[0045] Membrane stack configuration: Homogeneous cation exchange membranes (CM-7000) and homogeneous anion exchange membranes (AM-7000) are arranged alternately, with an effective membrane area of 0.5 m². 2 There are 20 pairs in total.
[0046] Operating parameters: Current density 450 A / m 2 Temperature 42℃, dilute / concentrate flow rate 2 cm / s, voltage gradient 1.8 V / pair of membrane.
[0047] Separation effect: Al3+ Retention rate: ≥92.8% (remaining in the dilute / source solution side); Fe 3+ Retention rate: ≥89.3%; TiO2 2+ Mobility: 80.5%, entering the concentration chamber for enrichment; ZrO 2+ Mobility: 81.1%; Rare earth ions (La) 3+ Ce 3+ Migration rate: 90.4%, entering the concentration chamber, total recovery rate 93.3%; Li + Ga 3+ Migration rate: >85.8%; Free acid recovery rate: 91.6% (the acid concentration recovered in the concentration chamber is 2.8 mol / L, which can be directly replenished and returned to the concentrated acid leaching).
[0048] Operational stability: After 168 hours of continuous operation, the membrane flux decreased by less than 10%, and recovered after cleaning.
[0049] Example 2 A sodium carbonate powder injection device was installed next to the soot blowing device at the ash outlet. Na2CO3 powder with a particle size <50μm was injected at 8% of the fly ash mass. Compressed air was used as the conveying air source, and the mixture was mixed and reacted at 700℃ for 4 hours. The modified fly ash was then collected. X-ray diffraction analysis was performed on the obtained modified fly ash, and the results are shown in Table 1.
[0050] The modified fly ash was mixed with deionized water at a mass ratio of 1:4, stirred at 80℃ for 1 hour, and then filtered for the first time. The resulting water leachate contained K. + Na + The high concentration is returned to the powder preparation system as a carrier for the powder injection system or used to prepare the leaching agent; the water-leached solid obtained from the first filtration is mixed with hydrochloric acid (0.3 mol / L) at a mass ratio of 1:3, stirred at 85℃ for 2 hours, and then filtered a second time. The resulting dilute acid leachate (containing Fe) 3+ Al 3+ Hydrochloric acid is added until the HCl concentration in the dilute acid leachate reaches 0.3 mol / L, then the solution is recycled. The dilute acid leachate solid obtained from the second filtration is mixed with hydrochloric acid (6 mol / L) at a mass ratio of 1:2, stirred at 90℃ for 5 hours, and then filtered a third time. The concentrated acid leachate solid obtained from the third filtration is washed and dried to obtain a product with a SiO2 content of 84.2%, which is then granulated and used for wheat application. The concentrated acid leachate obtained from the third filtration is sent to an ion-exchange membrane electrodialysis unit. The rare earth enrichment solution is precipitated to obtain mixed rare earth oxides with a purity ≥86%. The acid solution is recovered and returned to the concentrated acid leachate process. For every ton of fly ash processed, only 200 kg of concentrated acid and a small amount of sodium carbonate (20% of the initial amount) are added to the entire system, with no wastewater discharge.
[0051] The operating parameters and effects of ion-exchange membrane separation in this embodiment are as follows: The concentrated acid leaching solution (Al) of this embodiment 3+ 28.7 g / L, Fe 3+ 8.3 g / L, TiO 2+ 1.7 g / L, ZrO 2+ 0.51 g / L (total rare earth 789.2 mg / L) was fed into the ion-exchange membrane electrodialysis system.
[0052] Membrane stack configuration: Homogeneous cation exchange membranes (CM-7000) and homogeneous anion exchange membranes (AM-7000) are arranged alternately, with an effective membrane area of 0.5 m². 2 There are 20 pairs in total.
[0053] Operating parameters: Current density 450 A / m 2 Temperature 42℃, dilute / concentrate flow rate 2 cm / s, voltage gradient 1.8 V / pair of membrane.
[0054] Separation effect: Al 3+ Retention rate: ≥93.5% (remaining in the dilute / original solution side); Fe 3+ Retention rate: ≥90.2%; TiO2 2+ Mobility: 78%, entering the concentration chamber for enrichment; ZrO 2+ Mobility: 80.7%; Rare earth ions (La) 3+ Ce 3+ Migration rate: 91.9%, entering the concentration chamber, total recovery rate 94.2%; Li + Ga 3+ Migration rate: >84.4%; Free acid recovery rate: 92.2% (the concentration of acid recovered in the concentration chamber is 3.9 mol / L, which can be directly replenished and returned to the concentrated acid leaching).
[0055] Operational stability: After 168 hours of continuous operation, the membrane flux decreased by less than 10%, and recovered after cleaning.
[0056] Example 3 A sodium carbonate powder injection device was installed next to the soot blowing device at the ash outlet. Na2CO3 powder with a particle size <50μm was injected at 10% of the fly ash mass. Compressed air was used as the conveying air source, and the mixture was mixed and reacted at 750℃ for 5 hours. The modified fly ash was then collected. X-ray diffraction analysis was performed on the obtained modified fly ash, and the results are shown in Table 1.
[0057] The modified fly ash was mixed with deionized water at a mass ratio of 1:4, stirred at 90°C for 2 hours, and then filtered for the first time. The resulting water leachate contained K. + Na +The concentration is relatively high, and it is returned to the powder preparation system as a carrier for the powder injection system or used to prepare the leaching agent; the water-leached solids obtained from the first filtration are mixed with hydrochloric acid (0.2 mol / L) at a mass ratio of 1:5, stirred at 85℃ for 2 hours, and then filtered a second time. The resulting dilute acid leachate (containing Fe) 3+ Al 3+ Hydrochloric acid is added until the HCl concentration in the dilute acid leachate reaches 0.2 mol / L, then the solution is recycled. The dilute acid leachate solid obtained from the second filtration is mixed with hydrochloric acid (7 mol / L) at a mass ratio of 1:2, stirred at 90℃ for 4 hours, and then filtered a third time. The concentrated acid leachate solid obtained from the third filtration is washed and dried to obtain a product with a SiO2 content of 86.3%, which is then granulated and used for wheat application. The concentrated acid leachate obtained from the third filtration is sent to an ion-exchange membrane electrodialysis unit. The rare earth enrichment solution is precipitated to obtain mixed rare earth oxides with a purity ≥85.5%. The acid solution is recovered and returned to the concentrated acid leachate process. The entire system requires only 210 kg of concentrated acid and a small amount of sodium carbonate (21% of the initial amount) to be added for every ton of fly ash processed, with no wastewater discharge.
[0058] The operating parameters and effects of ion-exchange membrane separation in this embodiment are as follows: The concentrated acid leaching solution (Al) of this embodiment 3+ 39.6 g / L, Fe 3+ 8.5 g / L, TiO 2+ 1.5g / L, ZrO 2+ (0.43 g / L, total rare earth content 890.4 mg / L) was fed into the ion-exchange membrane electrodialysis system.
[0059] Membrane stack configuration: Homogeneous cation exchange membranes (CM-7000) and homogeneous anion exchange membranes (AM-7000) are arranged alternately, with an effective membrane area of 0.5 m². 2 There are 20 pairs in total.
[0060] Operating parameters: Current density 450 A / m 2 Temperature 42℃, dilute / concentrate flow rate 2 cm / s, voltage gradient 1.8 V / pair of membrane.
[0061] Separation effect: Al 3+ Retention rate: ≥92.7% (remaining in the dilute / source solution side); Fe 3+ Retention rate: ≥90.6%; TiO2 2+ Mobility: 78.9%, entering the concentration chamber for enrichment; ZrO 2+ Mobility: 82.4%; Rare earth ions (La) 3+ Ce 3+ Migration rate: 91.5%, entering the concentration chamber, total recovery rate 93.8%; Li + Ga 3+Migration rate: >86.7%; Free acid recovery rate: 94.4% (the concentration of acid recovered in the concentration chamber is 4.1 mol / L, which can be directly replenished and returned to the concentrated acid leaching).
[0062] Operational stability: After 168 hours of continuous operation, the membrane flux decreased by less than 10%, and recovered after cleaning.
[0063] Example 4 A sodium carbonate powder injection device was installed next to the soot blowing device at the ash outlet. Na2CO3 powder with a particle size <50μm was injected at 12% of the fly ash mass. Compressed air was used as the conveying air source, and the mixture was mixed and reacted at 800℃ for 3 hours. The modified fly ash was then collected. X-ray diffraction analysis was performed on the obtained modified fly ash, and the results are shown in Table 1.
[0064] The modified fly ash was mixed with deionized water at a mass ratio of 1:4, stirred at 80°C for 1 hour, and then filtered for the first time. The resulting water leachate contained K. + Na + The high concentration is returned to the powder preparation system as a carrier for the powder injection system or used to prepare the leaching agent; the water-leached solid obtained from the first filtration is mixed with hydrochloric acid (0.3 mol / L) at a mass ratio of 1:3, stirred at 75°C for 2 hours, and then filtered a second time. The resulting dilute acid leachate (containing Fe) 3+ Al 3+ Hydrochloric acid is added until the HCl concentration in the dilute acid leachate reaches 0.3 mol / L, then the solution is recycled. The dilute acid leachate solid obtained from the second filtration is mixed with hydrochloric acid (6 mol / L) at a mass ratio of 1:3, stirred at 90℃ for 5 hours, and then filtered a third time. The concentrated acid leachate solid obtained from the third filtration is washed and dried to obtain a product with a SiO2 content of 87.6%, which is then granulated and used for wheat application. The concentrated acid leachate obtained from the third filtration is sent to an ion-exchange membrane electrodialysis unit. The rare earth enrichment solution is precipitated to obtain mixed rare earth oxides with a purity ≥89%. The acid solution is recovered and returned to the concentrated acid leachate process. The entire system requires only 190 kg of concentrated acid and a small amount of sodium carbonate (15.8% of the initial amount) to be added for every ton of fly ash processed, with no wastewater discharge.
[0065] The operating parameters and effects of ion-exchange membrane separation in this embodiment are as follows: The concentrated acid leaching solution (Al) of this embodiment 3+ 21.2 g / L, Fe 3+ 3.9 g / L, TiO 2+ 0.62 g / L, ZrO 2+ (0.36 g / L, total rare earth content 490 mg / L) was fed into the ion-exchange membrane electrodialysis system.
[0066] Membrane stack configuration: Homogeneous cation exchange membranes (CM-7000) and homogeneous anion exchange membranes (AM-7000) are arranged alternately, with an effective membrane area of 0.5 m².2 There are 20 pairs in total.
[0067] Operating parameters: Current density 450 A / m 2 Temperature 42℃, dilute / concentrate flow rate 2 cm / s, voltage gradient 1.8 V / pair of membrane.
[0068] Separation effect: Al 3+ Retention rate: ≥92.2% (remaining in the dilute / original solution side); Fe 3+ Retention rate: ≥90.6%; TiO2 2+ Mobility: 81.7%, entering the concentration chamber for enrichment; ZrO 2+ Mobility: 82.3%; Rare earth ions (La) 3+ Ce 3+ Migration rate: 91.1%, entering the concentration chamber, total recovery rate 90.9%; Li + Ga 3+ Migration rate: >86.2%; Free acid recovery rate: 94% (acid concentration recovered in the concentration chamber is 2.9 mol / L, which can be directly replenished and returned to concentrated acid leaching).
[0069] Operational stability: After 168 hours of continuous operation, the membrane flux decreased by less than 10%, and recovered after cleaning.
[0070] Example 5 A sodium carbonate powder injection device was installed next to the soot blowing device at the ash outlet. NaCl powder with a particle size <50μm was injected at 2% of the fly ash mass. Compressed air was used as the conveying air source, and the mixture was reacted at 700℃ for 3 hours. The modified fly ash was then collected. X-ray diffraction analysis was performed on the obtained modified fly ash, and the results are shown in Table 1.
[0071] The modified fly ash was mixed with deionized water at a mass ratio of 1:3, stirred at 85°C for 1 hour, and then filtered for the first time. The resulting water leachate contained K. + Na + The high concentration is returned to the powder preparation system as a carrier for the powder injection system or used to prepare the leaching agent; the water-leached solid obtained from the first filtration is mixed with hydrochloric acid (0.6 mol / L) at a mass ratio of 1:3, stirred at 75°C for 2 hours, and then filtered a second time. The resulting dilute acid leachate (containing Fe) 3+ Al 3+Hydrochloric acid is added until the HCl concentration in the dilute acid leaching solution reaches 0.6 mol / L, then the solution is recycled. The dilute acid leaching solid obtained from the second filtration is mixed with hydrochloric acid (6 mol / L) at a mass ratio of 1:3, stirred at 90℃ for 5 hours, and then filtered a third time. The concentrated acid leaching solid obtained from the third filtration is washed and dried to obtain a product with a SiO2 content of 50.5%. The concentrated acid leaching solution obtained from the third filtration is sent to an ion-exchange membrane electrodialysis device. The rare earth enrichment solution is precipitated to obtain mixed rare earth oxides with a purity ≥45%. The acid solution is recovered and returned to the concentrated acid leaching process. The entire system only requires 290 kg of concentrated acid (hydrochloric acid calculated as HCl) and a small amount of sodium chloride (35% of the initial amount) to be added for every ton of fly ash processed. There is no wastewater discharge.
[0072] The operating parameters and effects of ion-exchange membrane separation in this embodiment are as follows: The concentrated acid leaching solution (Al) of this embodiment 3+ 10.9 g / L, Fe 3+ 2.5 g / L, TiO 2+ 0.6 g / L, ZrO 2+ 0.12 g / L (total rare earth 144 mg / L) was fed into the ion-exchange membrane electrodialysis system.
[0073] Membrane stack configuration: Homogeneous cation exchange membranes (CM-7000) and homogeneous anion exchange membranes (AM-7000) are arranged alternately, with an effective membrane area of 0.5 m². 2 There are 20 pairs in total.
[0074] Operating parameters: Current density 450 A / m 2 Temperature 42℃, dilute / concentrate flow rate 2 cm / s, voltage gradient 1.8 V / pair of membrane.
[0075] Separation effect: Al 3+ Retention rate: ≥92.7% (remaining in the dilute / source solution side); Fe 3+ Retention rate: ≥90.2%; TiO2 2+ Mobility: 83.6%, entering the concentration chamber for enrichment; ZrO 2+ Mobility: 84.9%; Rare earth ions (La) 3+ Ce 3+ Migration rate: 91.7%, entering the concentration chamber, total recovery rate 93.4%; Li + Ga 3+ Migration rate: >85.4%; Free acid recovery rate: 94% (acid concentration recovered in the concentration chamber is 3.8 mol / L, which can be directly replenished and returned to concentrated acid leaching).
[0076] Operational stability: After 168 hours of continuous operation, the membrane flux decreased by less than 10%, and recovered after cleaning.
[0077] Example 6 A sodium carbonate powder injection device was installed next to the soot blowing device at the ash outlet. KCl powder with a particle size <50 μm was injected at 3% of the fly ash mass. Compressed air was used as the conveying air source, and the mixture was reacted at 750℃ for 3 hours. The modified fly ash was collected. X-ray diffraction analysis was performed on the obtained modified fly ash, and the results are shown in Table 1.
[0078] The modified fly ash was mixed with deionized water at a mass ratio of 1:3, stirred at 90°C for 1 hour, and then filtered for the first time. The resulting water leachate contained K. + Na + The high concentration is returned to the powder preparation system as a carrier for the powder spraying system or used to prepare the leaching agent; the water-leached solids obtained from the first filtration are mixed with hydrochloric acid (0.4 mol / L) at a mass ratio of 1:3, stirred at 70°C for 2 hours, and then filtered a second time. The resulting dilute acid leachate (containing Fe) 3+ Al 3+ Hydrochloric acid is added until the HCl concentration in the dilute acid leaching solution reaches 0.4 mol / L, then the solution is recycled. The dilute acid leaching solid obtained from the second filtration is mixed with hydrochloric acid (6 mol / L) at a mass ratio of 1:3, stirred at 90℃ for 4 hours, and then filtered a third time. The concentrated acid leaching solid obtained from the third filtration is washed and dried to obtain a product with a SiO2 content of 43.1%. The concentrated acid leaching solution obtained from the third filtration is sent to an ion-exchange membrane electrodialysis device. The rare earth enrichment solution is precipitated to obtain mixed rare earth oxides with a purity ≥47%. The acid solution is recovered and returned to the concentrated acid leaching process. The entire system only requires 260 kg of concentrated acid and a small amount of KCl (27% of the initial amount) to be added for every ton of fly ash processed, with no wastewater discharge.
[0079] The operating parameters and effects of ion-exchange membrane separation in this embodiment are as follows: The concentrated acid leaching solution (Al) of this embodiment 3+ 11.7 g / L, Fe 3+ 1.6 g / L, TiO 2+ 0.67 g / L, ZrO 2+ 0.11 g / L (total rare earth 247 mg / L) was fed into the ion-exchange membrane electrodialysis system.
[0080] Membrane stack configuration: Homogeneous cation exchange membranes (CM-7000) and homogeneous anion exchange membranes (AM-7000) are arranged alternately, with an effective membrane area of 0.5 m². 2 There are 20 pairs in total.
[0081] Operating parameters: Current density 450 A / m 2 Temperature 42℃, dilute / concentrate flow rate 2 cm / s, voltage gradient 1.8 V / pair of membrane.
[0082] Separation effect: Al 3+Retention rate: ≥93.5% (remaining in the dilute / original solution side); Fe 3+ Retention rate: ≥91.2%; TiO2 2+ Mobility: 80.4%, entering the concentration chamber for enrichment; ZrO 2+ Mobility: 84.1%; Rare earth ions (La) 3+ Ce 3+ Migration rate: 92.7%, entering the concentration chamber, total recovery rate 93.1%; Li + Ga 3+ Migration rate: >86.3%; Free acid recovery rate: 95% (the acid concentration recovered in the concentration chamber is 3.9 mol / L, which can be directly replenished and returned to the concentrated acid leaching).
[0083] Operational stability: After 168 hours of continuous operation, the membrane flux decreased by less than 10%, and recovered after cleaning.
[0084] Example 7 A sodium carbonate powder injection device was installed next to the soot blowing device at the ash outlet. A mixed powder of Na₂CO₃ and 2% NaCl with a particle size <50 μm was injected at 6% of the fly ash mass. Compressed air was used as the conveying air source, and the mixture was reacted at approximately 720℃ for 3 hours. The modified fly ash was collected. X-ray diffraction analysis was performed on the obtained modified fly ash, and the results are shown in Table 1.
[0085] The modified fly ash was mixed with deionized water at a mass ratio of 1:3, stirred at 70°C for 1 hour, and then filtered for the first time. The resulting water leachate contained K. + Na + The high concentration is returned to the powder preparation system as a carrier for the powder spraying system or used to prepare the leaching agent; the water-leached solid obtained from the first filtration is mixed with hydrochloric acid (0.2 mol / L) at a mass ratio of 1:5, stirred at 75°C for 2 hours, and then filtered a second time. The resulting dilute acid leachate (containing Fe) 3+ Al 3+ Hydrochloric acid is added until the HCl concentration in the dilute acid leachate reaches 0.2 mol / L, then the solution is recycled. The dilute acid leachate solid obtained from the second filtration is mixed with hydrochloric acid (6 mol / L) at a mass ratio of 1:3, stirred at 90℃ for 3 hours, and then filtered a third time. The concentrated acid leachate solid obtained from the third filtration is washed and dried to obtain a product with a SiO2 content of 86.2%, which is then granulated and used for wheat application. The concentrated acid leachate obtained from the third filtration is sent to an ion-exchange membrane electrodialysis unit. The rare earth enrichment solution is precipitated to obtain mixed rare earth oxides with a purity ≥90%. The acid solution is recovered and returned to the concentrated acid leachate process. The entire system requires only 230 kg of concentrated acid and a small amount of sodium carbonate and NaCl (21% and 12% of the initial dosage, respectively) to be added for every ton of fly ash processed, with no wastewater discharge.
[0086] The operating parameters and effects of ion-exchange membrane separation in this embodiment are as follows: The concentrated acid leaching solution (Al) of this embodiment 3+ 16.7 g / L, Fe 3+ 2.9 g / L, TiO 2+ 0.7 g / L, ZrO 2+ (0.25 g / L, total rare earth content 390.2 mg / L) was fed into the ion-exchange membrane electrodialysis system.
[0087] Membrane stack configuration: Homogeneous cation exchange membranes (CM-7000) and homogeneous anion exchange membranes (AM-7000) are arranged alternately, with an effective membrane area of 0.5 m². 2 There are 20 pairs in total.
[0088] Operating parameters: Current density 450 A / m 2 Temperature 42℃, dilute / concentrate flow rate 2 cm / s, voltage gradient 1.8 V / pair of membrane.
[0089] Separation effect: Al 3+ Retention rate: ≥92.2% (remaining in the dilute / original solution side); Fe 3+ Retention rate: ≥90.5%; TiO2 2+ Mobility: 79.6%, entering the concentration chamber for enrichment; ZrO 2+ Mobility: 81.1%; Rare earth ions (La) 3+ Ce 3+ Migration rate: 90.7%, entering the concentration chamber, total recovery rate 91.5%; Li + Ga 3+ Migration rate: >86.4%; Free acid recovery rate: 94.2% (the acid concentration recovered in the concentration chamber is 2.9 mol / L, which can be directly replenished and returned to the concentrated acid leaching).
[0090] Operational stability: After 168 hours of continuous operation, the membrane flux decreased by less than 10%, and recovered after cleaning.
[0091] Example 8 A sodium carbonate powder injection device was installed next to the soot blowing device at the ash outlet. A K₂CO₃ + 2% KCl mixed powder with a particle size of <50 μm was injected at 8% of the fly ash mass. Compressed air was used as the conveying air source, and the mixture was reacted at 780℃ for 3 hours. The modified fly ash was then collected. X-ray diffraction analysis was performed on the obtained modified fly ash, and the results are shown in Table 1.
[0092] The modified fly ash was mixed with deionized water at a mass ratio of 1:3, stirred at 70°C for 1 hour, and then filtered for the first time. The resulting water leachate contained K. + Na +The high concentration is returned to the powder preparation system as a carrier for the powder injection system or used to prepare the leaching agent; the water-leached solid obtained from the first filtration is mixed with hydrochloric acid (0.6 mol / L) at a mass ratio of 1:3, stirred at 75°C for 2 hours, and then filtered a second time. The resulting dilute acid leachate (containing Fe) 3+ Al 3+ Hydrochloric acid is added until the HCl concentration in the dilute acid leachate reaches 0.6 mol / L, then the solution is recycled. The dilute acid leachate solid obtained from the second filtration is mixed with hydrochloric acid (5 mol / L) at a mass ratio of 1:3, stirred at 90℃ for 3 hours, and then filtered a third time. The concentrated acid leachate solid obtained from the third filtration is washed and dried to obtain a product with a SiO2 content of 90.5%, which is then granulated and used for wheat application. The concentrated acid leachate obtained from the third filtration is sent to an ion-exchange membrane electrodialysis unit. The rare earth enrichment solution is precipitated to obtain mixed rare earth oxides with a purity ≥92%. The acid solution is recovered and returned to the concentrated acid leachate process. The entire system only requires 280 kg of concentrated acid to be added for every ton of fly ash processed, along with small amounts of K2CO3 and KCl (24% and 13% of the initial dosage, respectively), with no wastewater discharge.
[0093] The operating parameters and effects of ion-exchange membrane separation in this embodiment are as follows: The concentrated acid leaching solution (Al) of this embodiment 3+ 18.5 g / L, Fe 3+ 3.2 g / L, TiO 2+ 0.8 g / L, ZrO 2+ 0.2 g / L (total rare earth 420 mg / L) was fed into the ion-exchange membrane electrodialysis system.
[0094] Membrane stack configuration: Homogeneous cation exchange membranes (CM-7000) and homogeneous anion exchange membranes (AM-7000) are arranged alternately, with an effective membrane area of 0.5 m². 2 There are 20 pairs in total.
[0095] Operating parameters: Current density 450 A / m 2 Temperature 42℃, dilute / concentrate flow rate 2 cm / s, voltage gradient 1.8 V / pair of membrane.
[0096] Separation effect: Al 3+ Retention rate: ≥92% (remaining in the dilute / concentrate side); Fe 3+ Retention rate: ≥89%; TiO 2+ Mobility: 76%, entering the concentration chamber for enrichment; ZrO 2+ Mobility: 81%; Rare earth ions (La) 3+ Ce 3+ Migration rate: 90%, entering the concentration chamber, total recovery rate 91%; Li + Ga 3+Migration rate: >85%; Free acid recovery rate: 94% (the acid concentration recovered in the concentration chamber is 4.2 mol / L, which can be directly replenished and returned to the concentrated acid leaching).
[0097] Operational stability: After 200 hours of continuous operation, the membrane flux decreased by less than 8%, and recovered after cleaning.
[0098] Example 9 Same as Example 8, except that hydrochloric acid is replaced with sulfuric acid in equal molar amounts. The specific operation is as follows: A sodium carbonate powder injection device was installed next to the soot blowing device at the ash outlet. A K₂CO₃ + 2% KCl mixed powder with a particle size of <50 μm was injected at 8% of the fly ash mass. Compressed air was used as the conveying air source, and the mixture was reacted at 780℃ for 3 hours. The modified fly ash was then collected. X-ray diffraction analysis was performed on the obtained modified fly ash, and the results are shown in Table 1.
[0099] The modified fly ash was mixed with deionized water at a mass ratio of 1:3, stirred at 70°C for 1 hour, and then filtered for the first time. The resulting water leachate contained K. + Na + The high concentration is returned to the powder preparation system as a carrier for the powder injection system or used to prepare the leaching agent; the water-leached solid obtained from the first filtration is mixed with sulfuric acid solution (0.6 mol / L) at a mass ratio of 1:3, stirred at 75°C for 2 hours, and then filtered a second time. The resulting dilute acid leachate (containing Fe) 3+ Al 3+ Sulfuric acid is added until the concentration of sulfuric acid in the dilute acid leachate is 0.6 mol / L, then recycled. The dilute acid leachate solid obtained from the second filtration is mixed with sulfuric acid solution (5 mol / L) at a mass ratio of 1:3, stirred at 90℃ for 3 hours, and then filtered a third time. The concentrated acid leachate solid obtained from the third filtration is washed and dried to obtain a product with a SiO2 content of 91%, which is then granulated and used for wheat application. The concentrated acid leachate obtained from the third filtration is sent to an ion-exchange membrane electrodialysis unit. The rare earth enrichment solution is precipitated to obtain mixed rare earth oxides with a purity ≥92%. The acid solution is recovered and returned to the concentrated acid leachate process. The entire system only requires 230 kg of concentrated acid to be added for every ton of fly ash processed, along with small amounts of K2CO3 and KCl (18% and 11% of the initial dosage, respectively), with no wastewater discharge.
[0100] The operating parameters and effects of ion-exchange membrane separation in this embodiment are as follows: The concentrated acid leaching solution (Al) of this embodiment 3+ 26.4 g / L, Fe 3+ 3.1 g / L, TiO 2+ 0.82 g / L, ZrO 2+ (0.19 g / L, total rare earth content 455 mg / L) was fed into the ion-exchange membrane electrodialysis system.
[0101] Membrane stack configuration: The membrane type is an acid-resistant bipolar membrane; Operating parameters: Current density 80 A / m 2 Temperature 35℃, dilute / concentrate flow rate 1.8 cm / s, voltage gradient 11.0 V / pair of membrane.
[0102] Separation effect: Al 3+ Retention rate: ≥90.6% (remaining in the dilute / source solution side); Fe 3+ Retention rate: ≥89.1%; TiO2 2+ Mobility: 81.3%, entering the concentration chamber for enrichment; ZrO 2+ Mobility: 82.2%; Rare earth ions (La) 3+ Ce 3+ Migration rate: 91.7%, entering the concentration chamber, total recovery rate 89.4%; Li + Ga 3+ Migration rate: >85.6%; Free acid recovery rate: 92.8% (the acid concentration recovered in the concentration chamber is 2.6 mol / L, which can be directly replenished and returned to the concentrated acid leaching).
[0103] Operational stability: After 168 hours of continuous operation, the membrane flux decreased by less than 10%, and recovered after cleaning.
[0104] Example 10 Same as Example 8, except that hydrochloric acid is replaced with nitric acid in equal molar amounts. The specific operation is as follows: A sodium carbonate powder injection device was installed next to the soot blowing device at the ash outlet. A K₂CO₃ + 2% KCl mixed powder with a particle size of <50 μm was injected at 8% of the fly ash mass. Compressed air was used as the conveying air source, and the mixture was reacted at 780℃ for 4 hours. The modified fly ash was then collected. X-ray diffraction analysis was performed on the obtained modified fly ash, and the results are shown in Table 1.
[0105] The modified fly ash was mixed with deionized water at a mass ratio of 1:3, stirred at 70°C for 1 hour, and then filtered for the first time. The resulting water leachate contained K. + Na + The high concentration is returned to the powder preparation system as a carrier for the powder injection system or used to prepare the leaching agent; the water-leached solid obtained from the first filtration is mixed with nitric acid solution (0.6 mol / L) at a mass ratio of 1:3, stirred at 75℃ for 2 hours, and then filtered a second time. The resulting dilute acid leachate (containing Fe) 3+ Al 3+Nitric acid is added to the dilute acid leachate until the concentration of nitric acid in the leachate is 0.6 mol / L, then recycled. The dilute acid leachate solid obtained from the second filtration is mixed with nitric acid solution (5 mol / L) at a mass ratio of 1:3, stirred at 90℃ for 3 hours, and then filtered a third time. The concentrated acid leachate solid obtained from the third filtration is washed and dried to obtain a product with a SiO2 content of 87.9%, which is then granulated and used for wheat application. The concentrated acid leachate obtained from the third filtration is sent to an ion-exchange membrane electrodialysis unit. The rare earth enrichment solution is precipitated to obtain mixed rare earth oxides with a purity ≥92.8%. The acid solution is recovered and returned to the concentrated acid leachate process. The entire system only requires 240 kg of concentrated acid to be added for every ton of fly ash processed, along with small amounts of K2CO3 and KCl (19% and 10% of the initial dosage, respectively), with no wastewater discharge.
[0106] The operating parameters and effects of ion-exchange membrane separation in this embodiment are as follows: The concentrated acid leaching solution (Al) of this embodiment 3+ 18.7 g / L, Fe 3+ 3.3 g / L, TiO 2+ 0.81 g / L, ZrO 2+ (0.19 g / L, total rare earth content 449 mg / L) was fed into the ion-exchange membrane electrodialysis system.
[0107] Membrane stack configuration: The membrane type is an acid-resistant bipolar membrane; Operating parameters: Current density 420 A / m 2 Temperature 40℃, dilute / concentrate flow rate 2 cm / s, voltage gradient 1.6 V / pair of membrane.
[0108] Separation effect: Al 3+ Retention rate: ≥90.5% (remaining in the dilute / source solution side); Fe 3+ Retention rate: ≥89.8%; TiO2 2+ Mobility: 80.1%, entering the concentration chamber for enrichment; ZrO 2+ Mobility: 82.3%; Rare earth ions (La) 3+ Ce 3+ Migration rate: 90.4%, entering the concentration chamber, total recovery rate 89.6%; Li + Ga 3+ Migration rate: >85.8%; Free acid recovery rate: 92% (acid concentration recovered in the concentration chamber is 2.2 mol / L, which can be directly replenished and returned to concentrated acid leaching).
[0109] Operational stability: After 168 hours of continuous operation, the membrane flux decreased by less than 10%, and recovered after cleaning.
[0110] Example 11 Same as Example 8, except that the scale of the experiment was increased to the pilot scale (1 ton of ash / batch), and the deviation of each indicator from Example 8 was <5%.
[0111] The modification conditions and modification effects of Examples 1 to 10 are shown in Table 1. In Examples 1 to 10, the Al2O3 leaching rate was determined by measuring the solid residue content (XRF) during the acid leaching stage; the rare earth leaching rate was determined by inductively coupled plasma mass spectrometry (ICP-MS) during the leachate stage. The total leaching rate was calculated based on the total Al2O3 or rare earth content in the original ash.
[0112] Table 1 Comparative Example 1 The cooled fly ash was collected at the ash outlet. The fly ash was mixed with deionized water at a mass ratio of 1:3, stirred at 70°C for 1 hour, filtered, and the resulting solid was subjected to X-ray diffraction analysis. The results are shown in Table 2.
[0113] The obtained solid was mixed with hydrochloric acid (0.5 mol / L) at a ratio of 1:3, stirred at 85°C for 2 hours, and filtered. The resulting solid was then mixed with hydrochloric acid (6 mol / L) at a mass ratio of 1:3, stirred at 90°C for 5 hours, and filtered. The obtained solid was washed and dried to obtain a product with a SiO2 content of 53.6%. The resulting concentrated acid leachate was sent to an ion-exchange membrane electrodialysis device. The rare earth enrichment solution was precipitated to obtain mixed rare earth oxides with a leaching rate of 28.6%.
[0114] Comparative Example 2 This comparative example uses the traditional method of first collecting ash, then mixing, and then calcining. The calcination temperature is 700℃ and the time is 3 hours. The specific process is as follows: Cooled fly ash was collected at the ash outlet and mixed with Na2CO3 powder at 5% of the fly ash mass. The mixture was reacted at 700℃ for 3 hours. The modified fly ash was then collected, and X-ray diffraction analysis was performed on the resulting modified fly ash. The results are shown in Table 2.
[0115] The modified fly ash was mixed with deionized water at a mass ratio of 1:3, stirred at 70°C for 1 hour, and filtered. The resulting solid was mixed with hydrochloric acid (0.6 mol / L) at a mass ratio of 1:3, stirred at 75°C for 2 hours, and filtered. The resulting solid was then mixed with hydrochloric acid (5 mol / L) at a mass ratio of 1:3, stirred at 90°C for 3 hours, and filtered. The resulting solid was washed and dried to obtain a product with a SiO2 content of 67.8%. The resulting concentrated acid leachate was sent to an ion-exchange membrane electrodialysis device. The rare earth enrichment solution was precipitated to obtain mixed rare earth oxides with a leaching rate of 48.9%.
[0116] Comparative Example 3 This comparative example uses the traditional method of first collecting ash, then mixing, and then calcining. The calcination temperature is 800℃ and the time is 2 hours. The specific process is as follows: Cooled fly ash was collected at the ash outlet and mixed with NaCl powder at 3% of the fly ash mass. The mixture was reacted at 800℃ for 2 hours. The modified fly ash was collected and X-ray diffraction analysis was performed on the obtained modified fly ash. The results are shown in Table 2.
[0117] The modified fly ash was mixed with deionized water at a mass ratio of 1:3, stirred at 70°C for 1 hour, and filtered. The resulting solid was mixed with hydrochloric acid (0.5 mol / L) at a mass ratio of 1:3, stirred at 75°C for 2 hours, and filtered. The resulting solid was then mixed with hydrochloric acid (6 mol / L) at a mass ratio of 1:3, stirred at 90°C for 4 hours, and filtered. The resulting solid was washed and dried to obtain a product with a SiO2 content of 55.6%. The resulting concentrated acid leachate was sent to an ion-exchange membrane electrodialysis device. The rare earth enrichment solution was precipitated to obtain mixed rare earth oxides with a leaching rate of 35.2%.
[0118] The experimental conditions and results of Comparative Examples 1 to 3 are shown in Table 2.
[0119] Table 2 The above are merely preferred embodiments of the present invention, but the scope of protection of the present invention is not limited thereto. Any variations or substitutions that can be easily conceived by those skilled in the art within the scope of the technology disclosed in the present invention should be included within the scope of protection of the present invention.
Claims
1. A method for modifying the process of fly ash outlet equipment in a coal-fired boiler, characterized in that, Includes the following steps: Functional powders are sprayed into the fly ash at the boiler ash outlet for high-temperature modification. The modified fly ash is then subjected to water leaching, dilute acid leaching, and concentrated acid leaching in sequence. The leachate from each stage is recycled. The solids from the concentrated acid leaching are used as silicon-based products. Rare earth elements, valuable metal ions, and acid are recovered from the obtained concentrated acid leaching solution. The functional powder is selected from one or both of neutral alkali metal salts and alkaline alkali metal salts.
2. The method for modifying the process of fly ash outlet equipment in a coal-fired boiler as described in claim 1, characterized in that, Specifically, the following steps are included: S1. Install a powder injection system on the ash blowing device at the ash outlet of a coal-fired boiler to inject functional powder into the fly ash and directly carry out the powder injection reaction in the high-temperature zone of the ash outlet to obtain modified fly ash. S2. The modified fly ash obtained in step S1 is subjected to water leaching treatment, and liquid-solid separation is performed to obtain water leaching liquid and water leaching solid; the water leaching liquid is returned to step S1 as a carrier of the powder injection system or used to prepare leaching agent. S3. The water-soaked solid obtained in step S2 is subjected to dilute acid leaching treatment, and the liquid and solid are separated to obtain dilute acid leaching solution and dilute acid leaching solid; acid is added to the dilute acid leaching solution and it is recycled in the dilute acid leaching treatment. S4. The dilute acid leaching solid obtained in step S3 is subjected to concentrated acid leaching treatment, and the liquid and solid are separated to obtain concentrated acid leaching solution and concentrated acid leaching solid. The obtained concentrated acid leaching solid is washed and dried and used as silicon-based nutrient fertilizer or soil conditioner. Rare earth elements, valuable metal ions and acid are recovered from the concentrated acid leaching solution using an ion membrane separation system. The separated acid solution is returned to step S4 for recycling.
3. The method for modifying the process of fly ash outlet equipment in a coal-fired boiler as described in claim 2, characterized in that, In step S1, the temperature of the high-temperature zone at the ash outlet is 650~800℃.
4. The method for modifying the process of fly ash outlet equipment in a coal-fired boiler as described in claim 2, characterized in that, In step S1, the neutral alkali metal salt includes NaCl and KCl; the alkaline alkali metal salt includes Na2CO3 and K2CO3. The amount of neutral alkali metal salt added is 2-3% of the mass of fly ash; the amount of alkaline alkali metal salt added is 6-12% of the mass of fly ash.
5. The method for modifying the process of fly ash outlet equipment in a coal-fired boiler as described in claim 2, characterized in that, In step S1, the particle size of the functional powder is <50 μm.
6. The method for modifying the process of fly ash outlet equipment in a coal-fired boiler of a thermal power plant according to claim 2, characterized in that, In step S2, the water immersion treatment is performed by mixing the modified fly ash and water at a mass ratio of 1:(3~4) and stirring at 70~90℃ for 1~2 h.
7. The method for modifying the process of fly ash outlet equipment in a coal-fired boiler as described in claim 2, characterized in that, In step S3, the dilute acid leaching process is performed by mixing the water-leached solid and dilute acid at a mass ratio of 1:(3~5) and stirring at 70~85°C for 2 hours.
8. The method for modifying the process of fly ash outlet equipment in a coal-fired boiler as described in claim 7, characterized in that, The dilute acid is selected from hydrochloric acid, sulfuric acid, or nitric acid; the concentration of the dilute acid is 0.2~0.6 mol / L.
9. The method for modifying the process of fly ash outlet equipment in a coal-fired boiler according to claim 2, characterized in that, In step S4, the concentrated acid leaching process is performed by mixing the dilute acid leaching solid and concentrated acid at a mass ratio of 1:(2~3) and stirring at 90°C for 3~5 h.
10. The method for modifying the process of fly ash outlet equipment in a coal-fired boiler of a thermal power plant according to claim 9, characterized in that, The concentrated acid is selected from hydrochloric acid, sulfuric acid, or nitric acid; the concentration of the concentrated acid is 5~7 mol / L.